2020
DOI: 10.1109/access.2020.2969270
|View full text |Cite
|
Sign up to set email alerts
|

A Public Psychological Pressure Index for Social Networks

Abstract: With the worldwide proliferation of social networks, public opinion analysis of data generated by social networks has become an important field of research. Social networks have become a major platform for public opinion formation and diffusion, and analyzing public opinion through social network data plays an important role across numerous fields, including political science, economics, commerce, finance, international trade, public policy implementation and so on. Nevertheless, the corresponding quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Density and reciprocity indicate a density and reciprocal relationship in a group in a communication network (Mendelsohn et al, 2021). Anies Baswedan Support Network has a low density value, it can be interpreted that the interaction of most Twitter account users on the hashtag Support Anies Baswedan is only limited to mentioning, retweeting, and replying in one direction to certain actors (Zhang et al, 2020). While actors who have many relationships do not reply or mention in response to the interaction given (Bennett & ISSN: 2723-7672 197 W: http://journal2.uad.ac.id/index.php/commicast/index | E: commicast@comm.uad.ac.id Entman, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Density and reciprocity indicate a density and reciprocal relationship in a group in a communication network (Mendelsohn et al, 2021). Anies Baswedan Support Network has a low density value, it can be interpreted that the interaction of most Twitter account users on the hashtag Support Anies Baswedan is only limited to mentioning, retweeting, and replying in one direction to certain actors (Zhang et al, 2020). While actors who have many relationships do not reply or mention in response to the interaction given (Bennett & ISSN: 2723-7672 197 W: http://journal2.uad.ac.id/index.php/commicast/index | E: commicast@comm.uad.ac.id Entman, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…It can also refer to various ways in which males exploit or oppress others through their societal privileges, such as masculine moral authority and property domination [9], [10], [11]. Certain patriarchal societies are patrilineal, which indicates that property and position are inherited through male ancestry [12]. This dominance is attributed to significant biological differences between men and women to explain and justify patriarchy.…”
Section: Introductionmentioning
confidence: 99%
“…Low level of cognition [ 20 ], insufficient information on pandemic prevention, history of chronic disease, and low resilience are also reasons that cannot be ignored that increase the risk of psychological disorders [ 21 ]. From the perspective of external factors, government information releases [ 22 ], social support [ 23 ], and public opinion [ 24 ] may have a significant impact on changes in people’s psychological state. In addition, studies also found that fear of the pandemic may be related to the workplace [ 25 ], and the nature of work is also related to the psychological pressure caused by the pandemic [ 26 ].…”
Section: Introductionmentioning
confidence: 99%